Aqueous power source integrated on a microfluidic chip - Song Yi Yeon; Yunju Kim; Chung Mu Kang; Sanguk Park; Taek Dong Chung (Proceedings of the National Academy of Sciences, 2025)
The growing demand for portable sensors for point-of-care (POC) and onsite health monitoring has led to significant interest in developing suitable power sources. In this study, we developed a microfluidic chip-integrated reverse electrodialysis (μRED) system for ecofriendly power generation with monolithic operation. Leveraging its fully ionic characteristic, μRED was successfully applied to an ionic diode, thereby demonstrating its capability for seamless integration. The feasibility of operating a bipolar electrode sensor without an external power supply was demonstrated, highlighting its broad applicability in electrochemical portable sensors. μRED has great potential for future applications, including electrochemical sensors for POC diagnostics and wearable devices.